Blockchain Solutions for Data Security in the Indian Vehicle Registration System - Othayoth, Sayuj (Digital Repository of Theses, 2025)
This dissertation investigates the application of blockchain technology to enhance data security and operational efficiency within the Indian vehicle registration system, focusing on the context of Kerala. The current system faces significant challenges, including data security vulnerabilities, document forgery, operational inefficiencies, and limited transparency, which impact government agencies, vehicle owners, and other stakeholders. This research aims to address these issues by exploring how blockchain’s inherent features—decentralization, immutability, and cryptographic security—can provide a robust solution. A mixed-methods research approach was employed, combining a comprehensive literature review with quantitative data from surveys (N=100 stakeholders including vehicle owners, professional drivers, automotive industry professionals, and government employees in Kerala) and qualitative insights from semi-structured interviews. A proof-of-concept (PoC) blockchain-based vehicle registration system was designed and developed on the BNS testnet to evaluate its practical feasibility and performance. The key findings demonstrate the technical viability of the blockchain solution and reveal significant improvements over traditional systems. The PoC exhibited enhanced data security. This study concludes that blockchain technology offers a secure, efficient, and viable solution for transforming the Indian vehicle registration system. The research provides practical recommendations for large-scale implementation, highlighting the potential for improved governance, enhanced citizen services, and significant fraud reduction. The findings contribute to the understanding of blockchain applications in public sector services and offer a pathway for digital transformation in managing critical government records.